2016
DOI: 10.1007/s10228-016-0543-6
|View full text |Cite
|
Sign up to set email alerts
|

Collection and aging of greater amberjack Seriola dumerili larvae and juveniles around the Penghu Islands, Taiwan

Abstract: 24In order to investigate the early life history of Seriola dumerili, we first validated otolith daily increments 25 using reared-fish (11-51 days after hatching). Four larval and early-juvenile S. dumerili were collected in May and July 26 2015 around the Penghu Islands, by surface larval net towing but not from 27 drifting seaweeds. Seriola dumerili were caught at thermal front, and total lengths and ages ranged 7.4-42.5 mm and 28 18-56 days, respectively. Our results indicate that the hatching dates of S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Our findings highlighted a significant relationship between observed S. dumerili catch rates and oceanic environments, with the species distributed from the southern part to the northern part across the TS. Hasegawa et al [13,16] reported that S. dumerili is a common species around the Taiwan Bank and distributed between the southern and northern parts of the TS. This study revealed that the predicted catch rates of S. dumerili distribution were highest in the northern region of TS during spring; the catch rates were high, and the area with high catch rates was widely distributed southward to northward during summer and comparatively, it predicted lower rates in autumn and increased predicted catch rates again in the southern part of TS, and relatively higher prediction in the northeastern part Taiwan but not matching the observed catch rates in the winter.…”
Section: Predicted Spatial Distribution Pattern Of the Greater Amberjackmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings highlighted a significant relationship between observed S. dumerili catch rates and oceanic environments, with the species distributed from the southern part to the northern part across the TS. Hasegawa et al [13,16] reported that S. dumerili is a common species around the Taiwan Bank and distributed between the southern and northern parts of the TS. This study revealed that the predicted catch rates of S. dumerili distribution were highest in the northern region of TS during spring; the catch rates were high, and the area with high catch rates was widely distributed southward to northward during summer and comparatively, it predicted lower rates in autumn and increased predicted catch rates again in the southern part of TS, and relatively higher prediction in the northeastern part Taiwan but not matching the observed catch rates in the winter.…”
Section: Predicted Spatial Distribution Pattern Of the Greater Amberjackmentioning
confidence: 99%
“…The greater amberjack (S. dumerili) is mainly distributed in temperate to tropical waters [12,13]. It is one of the most profitable commercial and recreational fish and a key aquaculture species [14][15][16]. Several populations of the species have been identified, two off the coast of the United States and two off the coast of East Asia in the East China Sea (ECS) and South China Sea (SCS) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed life history information is needed to effectively guide the fisheries management of this valuable resource. To date, the available life history data on the greater amberjack have been based almost entirely on assessments of the age, growth, mortality, and prey items of subadults and adults (Andaloro & Pipitone, 1997;Harris et al, 2007;Humphreys, 1980;Manooch & Potts, 1997;Sley et al, 2016;Thompson et al, 1999) and the early life history of juveniles (Deudero et al, 1999;Hasegawa et al, 2020;Hasegawa, Takatsuki, et al, 2017;Hasegawa, Yeh, et al, 2017;Wells & Rooker, 2004). Despite the importance of fish movements and migrations, data on adult greater amberjack are limited (Jackson et al, 2018;Murie et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The tropical and temperate species of genus Seriola are thought to have diverged 55 million years ago based on phylogenetic analysis (Swart et al, 2015). In addition, the spawning grounds of yellowtail (S. quinqueradiata) and greater amberjack in the ECS have been thought to differ based on the distribution of juveniles of both species (Hasegawa, Takatsuki, et al, 2017;Hasegawa, Yeh, et al, 2017;Nakada, 2008). These previous studies imply that the spawning grounds of both species may have changed recently.…”
Section: Introductionmentioning
confidence: 99%
“…To effectively develop strategies for managing this valuable fishery resource, information on the habitat preferences of and climate-related environmental effects on the fish is required. However, although fish habitat distribution and climate-related environmental effects have been reported to be essential factors affecting fish populations, the data available on the greater amberjack population in the waters of Taiwan are almost entirely based on assessments of age and growth (Hasegawa et al, 2017;Hasegawa et al, 2020), migration, and spawning (Tone et al, 2022).…”
Section: Introductionmentioning
confidence: 99%